Public Software: Quality Requirements Specification using LLMs and ISO 25000 - Saldarini, Javier (2025)
To implement innovative processes that facilitate operations for citizens, the development and implementation of software is essential as part of the digitalization of the State. In this regard, the National Office of Information Technology (ONTI) promotes a series of Technical Specifications (TS) to guide the development and/or acquisition of goods and services through the Technological Standards for Public Administration (ETAP). Specifically, the TS-LI, entitled: Software Development as a Technological Innovation Project, is a guide that serves as a reference for carrying out specifications for a technical requirement. Specifically, the main objective of this work is to present a guide that supports the activity of specifying software quality requirements, as a contribution to the TS-LI. The guide is based on the process proposed by the international standard ISO/IEC 25030 and proposes interaction with a generative AI agent based on LLM models, taking as reference the context of a specific project to be carried out, user stories, and the ISO/IEC 25000 family of standards. The proposal presented in this short article is part of a recently initiated line of research.